Elevated Serum Galectin-1 and Galectin-3 Levels in Children With Specific Learning Disorder: A Case Control Study - Tanır, Yaşar; Gülle, Zeynep Nur; Uncu, Gökçe Sultan; Baki, Adile Merve; Vural, Pervin; Soylu, Nusret; Örengül, Abdurrahman Cahid (Psychiatry investigation, 2023)
Objective Specific learning disorder (SLD) is a neurodevelopmental disorder in which underlying pathogenesis and etiological factors are not fully understood. Neuroinflammatory response (measured with serum levels of galectin-1 and galectin-3), which is associated with learning and memory, may play an important role in the etiopathogenesis of SLD. Aim of the present study is to examine whether serum galectin-1 and galectin-3 levels are related to SLD.Methods The current study consisted of 42 treatment-naive children with SLD and 42 control subjects. All of the subjects were assessed using semi-structured psychiatric examination to diagnose SLD and exclude attention-deficit hyperactivity disorder. Serum galectin-1 and galectin-3 levels were measured via venous blood samples.Results The SLD and control group did not differ significantly in terms of age, sex, and body mass index (BMI). The SLD group had significantly higher serum levels of galectin-1 (8.78±2.97 vs. 7.40±2.03, p=0.019) and galectin-3 (1.86±0.93 vs. 1.32±0.69, p=0.003) than the control group when controlled for age, sex, and BMI.Conclusion Higher serum levels of galectin-1 and galectin-3 in children with SLD may indicate the role of neuroinflammatory response in the pathogenesis of SLD. Other mechanisms involving galectin-1 and galectin-3 related to learning may play a part in the etiology of SLD.